Pengaruh Pertumbuhan Ekonomi, Pendapatan Asll Daerah, Dana Alokasi Umum dan Sisa Lebih Pembiayaan Anggaran Terhadap Pengalokaslan Belanja Modal - Mahmudi Mahmudi; Dewi Restiningrum (Jurnal Aplikasi Bisnis, 2017)
This research tries to identify the effect of economic growth, local government original revenue, general allocation grant,and remaining balance of local government budget for the year t towards the allocation of capital expenditure budget for the year t+1. This research used secondary data drawn from municipal budget realization report for the year 2003-2005 that was published by Central Bureau of Statistic. We used 108 local governments in Java as the sample of research. Based on regression analysis, the research shown the result that all independent variables, i.e. economic growth, local government original revenue, general allocation grant, and remaining balance of local government budget for the year t statistically significant affect the allocation of capital expenditure budget for the year t+1. It means that government officials for some extent consider past year data of economic growth level, local government original revenue, general allocation grant,and the remaining balance of budget to determine the allocation of next year capital expenditure budget.